Association between IV and topical tranexamic acid use and periprosthetic joint infections in hip and knee arthroplasty: a retrospective study - Yun-Chen Hsu; Allen Herng Shouh Hsu; Cheng-Ta Wu; Timothy L. Tan; Jun-Wen Wang; Feng-Chih Kuo (BMC Musculoskeletal Disorders)
Abstract Background Anemia and blood transfusions are recognized as risk factors for periprosthetic joint infections (PJI). Tranexamic acid (TXA) is established in reducing perioperative blood loss and transfusion requirements. Our study investigates the impact of perioperative TXA administration on the incidence of PJI in patients undergoing total joint arthroplasty (TJA) and evaluates the association of intravenous (IV) and topical applications with PJI occurrence. Methods A retrospective review was performed on 8042 patients who underwent primary total hip arthroplasty (THA) and knee arthroplasty (TKA) from January 2009 to December 2020, with a minimum one-year follow-up at our institution. We compared patients who received TXA (n = 3664, with 2345 receiving it IV and 1319 topically) to those who did not (n = 4378). 0.5–1.25 g of IV TXA was administered before skin incision, and 1.5–3 g of topical TXA was injected intra-articularly or into the drainage tube during surgery. The primary outcome was PJI development within one year, defined by the 2013 International Consensus Meeting criteria. Secondary outcomes included blood transfusion, hospital length of stay (LOS), venous thromboembolism (VTE), and 90-day readmission. We employed multivariate logistic regression and propensity score weighting to adjust for potential confounders and conducted subgroup analyses to assess PJI odds in TKA and THA patients treated with IV and topical TXA. Results The TXA group demonstrated a lower PJI occurrence (1.1% vs. 2.1%, p < 0.001), less blood transfusion (14.4% vs. 22.7%, p < 0.001) and shorter LOS (5.6 ± 1.6 vs. 6.5 ± 2.5, p < 0.001) compared to those without TXA. There was no difference between the two groups with regards to VTE and 90-day readmission. Perioperative TXA administration demonstrated lower PJI in multivariate analysis (OR 0.54, 95% CI 0.36–0.80, p = 0.002), and in propensity score weighting (OR 0.53, 95% CI 0.36–0.80, p = 0.002). In the subgroup analysis, both IV and topical administration of TXA resulted in decreased PJI (IV group: OR 0.53, 95% CI, 0.33–0.84, p = 0.007, topical group: OR 0.51, 95% CI, 0.29–0.89, p = 0.018), especially in primary TKA (IV TXA, OR 0.49, 95% CI, 0.29–0.83, p = 0.008; Topical TXA, OR, 0.56, 95% CI, 0.32–0.98, p = 0.042). Conclusion Perioperative TXA administration in primary hip and knee arthroplasty is significantly associated with a reduced PJI occurrence. Both IV and topical TXA routes showed similar association with reduced PJI occurrence, with a notable correlation observed in primary TKA.